(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper seeks to explore the Security and Privacy Challenges of Mobile Computing. Mobile computing has become ubiquitous, enabling users to access a vast array of services and information from anywhere at any time. This paradigm shift, facilitated by devices like smartphones and tablets connected via wireless networks, has revolutionized personal and professional interactions. However, the convenience and connectivity of mobile computing also bring significant security and privacy challenges that must be addressed to mitigate risks effectively. One of the primary challenges is the risk of device theft or loss. Mobile devices are easily misplaced or stolen, potentially exposing sensitive data and credentials if not adequately protected. Implementing robust authentication mechanisms such as strong passwords, biometric authentication, and remote wipe capabilities is crucial to prevent unauthorized access and mitigate the impact of device theft. Data encryption plays a pivotal role in safeguarding information both at rest and in transit. Encryption algorithms like AES ensure that even if data is intercepted, it remains unreadable without the decryption key. Mobile device manufacturers and app developers must prioritize encryption to protect user data from unauthorized access and breaches. App permissions present another significant challenge. Mobile apps often request access to sensitive data such as contacts, location information, and device sensors. Granting excessive permissions can compromise user privacy, as malicious apps may misuse this data. Users should carefully review and manage app permissions, granting only those necessary for the app’s intended functionality. The diversity of mobile platforms, including iOS and Android, complicates security efforts. Each platform has unique security features, update cycles, and vulnerabilities, requiring tailored security measures and regular updates to mitigate risks effectively. Moreover, the integration of Internet of Things (IoT) devices with mobile apps introduces additional security risks. IoT devices may lack robust security features, making them vulnerable to exploitation and potentially compromising data privacy.